Village fund for the community of Central Java free of stunting - Liya Desriyana (BKM Public Health and Community Medicine, 2021)
Objective : The purpose of this paper is to provide suggestions for activities using village funds to combat stunting Content : The problem of stunting if not handled properly will affect the economy of a nation because it produces a generation with low productivity. However, in reality the absorption of village funds for stunting prevention is still not optimal due to a lack of socialization and understanding of stunting programs in the regions. Human Development Cadres (KPM) under the supervision of regional apparatus are given an understanding of the task of increasing public awareness of stunting, identifying 1000 HPK household targets through social maps, facilitating villages to optimize stunting interventions using village funds, and receiving and reporting the results of monitoring growth and development. toddler babies.